An Assay of Antioxidant Power of Methanolic Extract Various Type of Soybean - Rika Yulia; Azminah Azminah; Michella Michella; Andre Tanzil (Jurnal Sains Farmasi & Klinis, 2015)
This study aimed to examine the antioxidant activity of methanolic extract of various type of soybean (Glycine max L.Merill) i.e Argomulyo, Burangrang, Ijen, and Kaba by using DPPH (1,1-Diphenyl-2-picryhydrazyl) method. The soybean was crushed, defatted using n-hexan, and extracted using methanol 90%. The processes of defatting and extracting were conducted by kinesthetic maceration. Identification of flavonoid content using KLT and an assay of the antioxidant power of soybean were carried out qualitatively and quantitavely. Qualitative analysis, the color of DPPH solution was fading from violet into yellowish. Quantitative analysis showed that the maximum wave-length of DPPH in methanol was 516,00 nm within 15-minute reaction time. The effective concentration 50% (EC50) of each extract was alsa determined. Results of this study revealed that the methanolic extract of soybean taken from varieties of Argomulyo, Burangrang, Ijen, and Kaba contained flavonoid, with EC50 value of each variety subsequently ranging from 3620.22 bpj; 5290.71 bpj; 4145.99 bpj; and 4253.50 bpj. Argomulyo variety showed the highest antioxidant power.